Jacques Rancière's Epistemological Analysis of Louis Althusser's Structural Marxism and Its Implications for Character Education at St. Thomas 1 High School, Medan - Benediktus Sipandi Ginggar; Petra Putri Sarinah Pandiangan (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This paper critically examines Jacques Rancière's rejection of Althusser's concept of interpretation in epistemological rupture, and explores its implications for character education at SMA St. Thomas 1 Medan. Rancière's critique stems from his rejection of hierarchical epistemological structures in the dichotomy between science and ideology. For Rancière, this approach constrains the division of social aesthetics of class outside of power as an ideological object, rather than as an autonomous political subject. By connecting this epistemological critique to the practice of character education, this paper argues that Rancière's principle of epistemic equality provides a theoretical foundation for building more inclusive and emancipatory learning environments. At SMA St. Thomas 1 Medan, character education that is grounded in critical reflection, autonomous thinking, and the equal recognition of all students as active moral agents aligns with Rancière's post-structural vision. The author uses a qualitative hermeneutic method to analyze primary works of Rancière and Althusser and relate them to current educational practice. Results affirm that the interpretation of Marxism must be grounded within social aesthetics, and that this framework offers a progressive, emancipatory model for character formation in secondary schools.